2006
DOI: 10.1111/j.1467-8683.2006.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Privatisation in Developing Countries

Abstract: We survey empirical studies examining privatisation's effects in developing economies. Most of these studies find that privatisation yields improvements in the operating and financial performance of divested firms, and only a handful document outright performance declines after privatisation. Almost all studies that examine post-privatisation changes in output, efficiency, profitability, capital investment spending and leverage document significant increases in the first four measures and significant declines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 82 publications
(142 reference statements)
1
41
0
Order By: Relevance
“…of state-owned shares in China (Ding & Graham, 2007); and excessive returns for owners where weak markets and little competition prevail (Megginson & Sutter, 2006;Parker & Kirkpatrick, 2005). The WB, IMF and Northern donors like USAID have been accused of ignoring local resistance to privatisation; employing inadequate financial systems for equity sales; ignoring local needs; and neglecting adequate regulation.…”
Section: Propagating Private Ownership: Privatisations and Multi-natmentioning
confidence: 99%
“…of state-owned shares in China (Ding & Graham, 2007); and excessive returns for owners where weak markets and little competition prevail (Megginson & Sutter, 2006;Parker & Kirkpatrick, 2005). The WB, IMF and Northern donors like USAID have been accused of ignoring local resistance to privatisation; employing inadequate financial systems for equity sales; ignoring local needs; and neglecting adequate regulation.…”
Section: Propagating Private Ownership: Privatisations and Multi-natmentioning
confidence: 99%
“…Theoretically, the privatised firms are supposed to use the available resources more efficiently as a law of nature (Seock, 2005). As was shown in the previous discussion, a number of studies showed the effectiveness of privatisation in improving the firm performance, while other studies came to opposite conclusions (Megginson & Sutter, 2006). It is not sufficient to view the transfer of ownership from public to private sector as an end in itself.…”
Section: Developing the Research Modelmentioning
confidence: 87%
“…Macro-level and institutional factors, such as market development and liberalisation, are likely to be the key determinants of post-privatisation performance in developing countries. Due to a variety of reasons, particularly the lack of high-quality data, the experience in developing countries is much less well researched (Parker & Kirkpatrick, 2007;Megginson & Sutter, 2006). These findings imply the need to examine the importance of institutional factors and their interactions with endowments and policies.…”
Section: Dynamic Comparisonsmentioning
confidence: 99%
See 2 more Smart Citations